The early Wittgenstein on religion - Lazenby, J. Mark (Continuum studies in British philosophy., 2006)
Many have observed how Wittgenstein's later philosophy illuminates the philosophy of religion. Rarely, however, have they paid attention to his early philosophy. Those who have argued that Wittgenstein refuted his early positions in his later work. This book proves otherwise. The proof is found in the answer to an important, but largely ignored, question: what is the relation of Wittgenstein's discussion of logic to his discussion of religion and ethics in the early work?¨Lazenby's answer is that Wittgenstein, in his discussion of logic, describes the boundaries of factual discourse for.